Problem aspects of the state standardization of modern dwelling-houses with the flats of «SMART» type: state in Ukraine and foreign experience (Environment & Health, 2019)
Objective: We carried out a hygienic assessment of the design of the blocks of flats with one-room flats for one person's residence on a compliance with the domestic and foreign norms of sanitary and town-planning legislation.Methods: In the work, we applied theoretical and analytical methods and method of sanitary-and-epidemiological examination of construction designs.Results: The current sanitary and town-planning legislation of Ukraine and foreign experience, concerning the construction of modern dwelling-houses with one-room flat of «smart» type for the residence of one person, were analyzed in the course of research.There is no practice and relevant regulatory documents for a design of one-room flats of a small area for one person's residence in Ukraine.According to the results of research, hygienic recommendations were developed to ensure optimum living conditions, including: a compliance with the domestic hygienic standards: the duration of insolation and natural light; the allowable concentrations of the chemicals in the air; the allowable levels of temperature, humidity, air ionization, noise, vibration, ionizing, and non-ionizing radiation; the content of radon, aerosol, including aerosols of biological origin, in the indoor air; the allowable levels of the bacterial pollution of air and surfaces; ensuring the compliance with the regulatory parameters of microclimate and air quality in the living room by the delimitation of the kitchen area from the living area with a kitchen-niches device with a mechanical plenum-exhaust ventilation and only with electric stoves; ensuring the volume of living space at the level of domestic standards - 75 m3, while the height of the room should be at least 2.75 m; the provision of a necessary set of the rooms with an area of the living room - 18 m2, the corridor - 3.9 m2, the bathroom - 3.4 m2, the balcony / loggia - 4.5 m2 to increase the level of comfort.Conclusions: According to the results of scientific research, a sanitary-and-epidemiological component was developed for a design of «smart» flat, and a possibility for the standardization (normalization) of the area of one-room flats for the residence of one person was preliminary substantiated.
Keywords: construction designs; modern residential buildings; flat of «smart» type; national and foreign state standards; sanitary-and-epidemiological living conditions